Dila ng bayan - Medina, Isagani Ramos 1930- (Mga ani ni Gani series, 2005)
"Dila ng Bayan is a collection of three interrrelated articles on language history and culture by Dr. Isagani R. Medina, professor emeritus, U.P. Department of History, College of Social Sciences and Philosophy. He himself gave the title for this book, which forms part of the "Mga Ani ni Gani" Series---a five-volume compilation of his essays written from 1951 to 1995."--Preface.